Aquatic plants of the Far East of Russia: a review on their use in medicine, pharmacological activity (Bangladesh Journal of Medical Science, 2015)
The review provides information on the medicine application of 30 aquatic plant taxa growing in the Russian Far East, and the prospects for their practical use. A list of aquatic plants on the pharmacotherapeutic action is done. The greatest number of species of aquatic plants has analgesic, antipyretic, anti-inflammatory, stomach and antidiarrheal, wound-healing properties. It is revealed that the most widely in traditional medicine in Asia and Europe are used Nelumbo nucifera, Trapa natans, representatives of the family Lemnaceae, Nymphaeaceae, genus Potamogeton. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21554 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.9-13